A Pseudo Random Bit Generator Based on Chaotic Logistic Map and its Statistical Testing - Patidar, V.; Sud, K.K.; Pareek, N.K. (Informatica)
A Pseudo Random Bit Generator Based on Chaotic Logistic Map and its Statistical Testing